Evaluation of Biological Activity of a Diazocine Derivative against Heart Failure Using an Ischemia-Reperfusion Injury Model - Lauro, Figueroa-Valverde; Marcela, Rosas-Nexticapa; Maria, López-Ramos; Magdalena, Alvarez-Ramirez; Virginia, Mateu-Armad Maria; Francisco, Díaz-Cedillo; Alejandra, Garcimarrero-Espino; Tomas, Lopez Gutierrez; Montserrat, Melgarejo-Gutierrez (Drug Research, 2022)
Background There are studies, which suggest that some diazocine derivatives can exert effects on the cardiovascular system; however, these effects are not very clear.Objective The aim of this research was to evaluate the biological activity of a diazocine derivative against heart failure translated as area infarct.Methods Biological activity produced by diazocine derivatives against heart failure was determinate using an ischemia/reperfusion injury model. Besides, to characterize the molecular mechanism of effect exerted by diazocine derivative on left ventricular pressure (LVP) was determinate in an isolated rat heart model using nifedipine, PINAME TXA2, and quinalizarin as controls.Results The results showed that diazocine derivative decrease the infarct area and increase the LVP. However, the effect produced by diazocine derivative on LVP was inhibited in the presence of quinalizarin.Conclusions The results indicate that biological activity produced by diazocine derivative on left ventricular pressure is through protein CK2 activation; this phenomenon could be translated as a decrease in both infarct area and heart failure.
Keywords: Diazocine; infarct area; heart failure; protein CK2